Optimizing Carding Speed Parameters and C-60 RSB Draft to Improve Sliver Quality - Addisu Temesgen Alamirew; Getnet Belay Tesema (Journal of Natural Fibers)
The optimization of settings of spinning machinery is one of the technically most urgent tasks when it comes to achieving the best possible raw material utilization for a high-quality yarn. Carding, as part of an integrated draw frame, is the very critical process in spinning preparation for open end rotor spun yarn manufacturing. The aim of the integrated draw frame process in a spinning line is to produce uniform slivers (with low deviation in mass per unit length) where the fibers are laid parallel and the sliver has relatively low neps, short fiber, trash and dust contents. This work examined the potential effects of a range of speed settings on the physical properties of sliver. Optimization results of the study showed that 3.5 CVm% and 2.8 U% of sliver achieved with 96.3% desirability with optimum predicted value of neps 252 cnt/g, short fiber content by number 25.8%, trash 29 cnt/g and dust 234 cnt/g satisfied at licker in speed of 1250 rpm, cylinder speed of 650 rpm, flat speed 0.29 m/min, and C 60 RSB total draft of 2.11 for processing the cotton variety of Deltapine 90 (DP-90).